PENINGKATAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA BARU SUNGAI MEDANG KECAMATAN AIR HANGAT TIMUR KABUPATEN KERINCI: AWAL KHAIRI, S.Sos., M.A.P - AWAL KHAIRI, S.Sos., M.A.P (JURNAL ADMINISTRASI NUSANTARA, 2022)
This study took place in the village of Baru Sungai Medang East Warm Water District Kerinci. Objective To determine the Improvement of Public Participation in the Construction of New Village in Sungai Medang East Warm Water District. The approach used in this study is qualitative. The Informant Research numbering as many as eight people. Techniques and Data Collection Tools in this study were interviews, observation and documentation. Tools Data Collection Form a list of questions, a pen, a book / paper, tape recorder. Analysis of individual government units are under construction in the village of Baru Sungai Medang East Warm Water District Kerinci. Results showed Increased Public Participation in New Village In development Medang River East Warm Water District Kerinci district has been running optimally. In carrying development already well underway, but there is increase the participation of the communities associated with the financing is not just a funding from the government but also non-governmental, it shows a form part of public participation in the process of development or awareness that in a development requires adequate funding and society in contributing not for the insistence of the government or other parties but for their consciousness to develop their regions. Where the rural village of Baru Sungai Medang East Warm Water District Kerinci development have ups and downs there needs to be improvement in the work program of the villag head and the village of Baru Sungai Medang.